Presentation of Environmental Elements in the Poetry of Mubashir Saeed (Environmental Critical Studies) - Ajmal, Shoaib (sourcecoder, 2023)
Mubashir Saeed holds the foot of the tradition and moves towards new paths that are in many landscapes. Mubashir Saeed portrays these scenes and expands the poetry intellectually. One of the stops along the way is the ecology. The topic of Eco-criticism hopes for a person to admit his mistake and give equal rights to other living beings and not recognize himself as superior to all other life. Because the consequences of human superiority are very serious in nature. In his poetry, Mubashir Saeed said has convinced man of his limitations in a loving and compassionate manner. So that humans and other species can live together in a rapidly changing world.